The Effect Of Mega-Projects On Sustainable Urban Development From The Perspective Of Citizens (Case Study: Padideh Tourism Complex Of Shandiz) - Anabestani, Zahra; Sarvar, Rahim; Hajiluie, Mas’oud Mahdavi (The Turkish Online Journal of Design Art and Communication, 2016)
Presence of a metropolitan project (megaproject) at a national scale would bring a considerable transformation in different scales of life of citizens in an urban settlement. This paper has been conducted to assess the effect of presence and activity of tourism complex of Padideh on sustainable development in Shandiz during 2009-2015 from the perspective of citizens. Methodology of this study in terms of objective is applied and is analytical-descriptive in terms of method; data collection method has been library and survey (questionnaire) method and data analysis has been conducted through descriptive statistics (mean, standard deviation) and inferential statistics (one sample and paired t-test, analysis of gray relational rating and structural equation). Statistical population of this study includes families living in Shandiz City with 5110 households. Statistical population of this study includes households of city of Shandiz with 5110 households and 17378 people based on the census of 2011; sample size of this study is obtained to 236 households based on Chochran formula. The obtained results of this study indicates that effects of presence and activities of tourism complex of Padideh in city of Shandiz with statistical value of 24/15 has had the most effect on economic aspect during studied time interval and social motivation, price of land and housing and profitability among indices have been more effected by this megaproject from the perspective of citizens. There are some recommendations in accordance with the findings of this study including strategies of urban managers in relation with changes in future market of land and housing, preparing some fields to attract tourists, paying attention to social conflicts and preventing them from occurrence, and preparing infrastructures etc.
Keywords: tourism complex of Padideh; economic aspect; social motivations; physical aspect; city of Shandiz